EXPERIMENTAL STUDY OF WEAR IN SHEET METAL DURING VARIOUS FORCES - Kumar Ahirwar, Rakesh; Jain, A.K. (International Journal of Research -GRANTHAALAYAH, 2017)
The experiments are conducted for different clearances between punch and die. It is observed that, beyond a clearance for each thickness of the steel sheet metal, however, below the critical clearance, scratches on the surface of the sheet metal were seen due to wear. Sheet metal is metal formed by an industrial process into thin, flat pieces. It is one of the fundamental forms used in metalworking and it can be cut and bent into a variety of shapes.